Cape Verdean blues - Barbosa, Shauna (Pitt poetry series., 2018)
The speaker in Cape Verdean Blues is an oracle walking down the street. Shauna Barbosa interrogates encounters and the weight of their space. Grounded in bodily experience and the phenomenology of femininity, this collection provides a sense of Cape Verdean identity. It uniquely captures the essence of "Sodade," as it refers to the Cape Verdean American experience, and also the nostalgia and self-reflection one navigates through relationships lived, lost, and imagined. And its layers of unusual imagery and sound hold the reader in their grip